Progression criteria in loading exercise programmes in lower limb tendinopathy: a protocol for a systematic review and meta-analysis. - Escriche-Escuder, Adrián; Casaña, José; Cuesta-Vargas, Antonio (BMJ, 2019)
Introduction: Lower limb tendinopathies have high rates of incidence and prevalence. Their symptomatology affects the functional capacity of people to exercise and work, being an important cause of economic and social burden. The evidence from the last decades points to therapeutic exercise as the first-line treatment in tendinopathies due to its good short-term and long-term clinical outcomes. However, there is no consensus about how the load progression should be managed throughout the therapeutic exercise programmes. Methods and analysis: This systematic review will be conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The present protocol has been registered in the International Prospective Register of Systematic Reviews (PROSPERO). The search will be performed through PubMed and Scopus by two reviewers, including references, from inception to 31 August 2019. It will include randomised controlled trials that: included patients with Achilles, patellar or gluteal tendinopathy; assessed pain, function or performance; and included at least one group where progressive physical exercise was administered as monotherapy. The quality of the studies included will be assessed using the Physiotherapy Evidence Database scale. The Grading of Recommendations, Assessment, Development and Evaluation Working Group approach will be used to assess the quality of the evidence. A meta-analysis will be performed if there is sufficient homogeneity across the interventions and outcomes measures to ensure pooling. Ethics and dissemination: Ethical approval is not necessary for this systematic review protocol. Regardless of its nature, the results obtained in this study will be published in a peer-reviewed journal and presented at a relevant conference.
Keywords: Aquiles, Tendón de - Lesiones y heridas; Ejercicio físico; Fisioterapia; Tendones - Lesiones y heridas; Revisiones sistemáticas (Medicina); Achilles tendinopathy; Dose; Exercise prescription; Gluteal tendinopathy; Systematic review